The Effect of Diagnostic Ureterorenoscopy on Intravesical Recurrence in Patients Undergoing Nephroureterectomy for Primary Upper Tract Urinary Carcinoma - TİNAY, İLKER (KARGER, 2021)
Objective: The objective of this study is to evaluate the effect of diagnostic ureterorenoscopy (URS) prior to radical nephroureterectomy (RNU) on intravesical recurrence (IVR), in patients with primary upper urinary tract urothelial carcinoma (UTUC). Materials and Methods: Retrospective analysis of 354 patients, who underwent RNU for UTUC from 10 urology centers between 2005 and 2019, was performed. The primary endpoint was the occurrence of IVR after RNU. Patients were divided into URS prior to RNU (Group 1) and no URS prior to RNU (Group 2). Rates of IVR after RNU were compared, and a Cox proportional hazards model was used to evaluate potential predictors of IVR. Results: After exclusion, a total of 194 patients were analyzed: Group 1 n = 95 (49.0%) and Group 2 n = 99 (51.0%). In Group 1, a tumor biopsy and histopathological confirmation during URS were performed in 58 (61.1%). The mean follow-up was 39.17 +/- 39.3 (range 12-250) months. In 54 (27.8%) patients, IVR was recorded after RNU, and the median recurrence time within the bladder was 10.0 (3-144) months. IVR rate was 38.9% in Group 1 versus 17.2% in Group 2 (p = 0.001). In Group 1, IVR rate was 43.1% in those undergoing intraoperative biopsy versus 32.4% of patients without biopsy during diagnostic URS (p =0.29). Intravesical recurrence-free survival (IRFS) was longer in Group 2 compared to Group 1 (median IRFS was 111 vs. 60 months in Groups 2 and 1, respectively (p< 0.001)). Univariate analysis revealed that IRFS was significantly associated with URS prior to RNU (HR: 2.9, 95% CI 1.65-5.41; p < 0.001). In multivariate analysis, URS prior to RNU (HR: 3.5, 95% CI 1.74-7.16; p < 0.001) was found to be an independent prognostic factor for IRFS. Conclusion: Diagnostic URS was associated with the poor IRFS following RNU for primary UTUC. The decision for a diagnostic URS with or without tumor biopsy should be reserved for cases where this information might influence further treatment decisions.
Keywords: Upper urinary tract; Urothelial carcinoma; Diagnostic ureterorenoscopy; Radical nephroureterectomy; Intravesical recurrence; TRANSITIONAL-CELL-CARCINOMA; UROTHELIAL CARCINOMA; RADICAL NEPHROURETERECTOMY; URETEROSCOPIC BIOPSY; ONCOLOGICAL OUTCOMES; IMPACT; BLADDER; PREDICTORS; MANAGEMENT